2021
DOI: 10.1590/1414-431x2020e11028
|View full text |Cite
|
Sign up to set email alerts
|

Engeletin protects against cerebral ischemia/reperfusion injury by modulating the VEGF/vasohibin and Ang-1/Tie-2 pathways

Abstract: Engeletin is a natural derivative of Smilax glabra rhizomilax that exhibits anti-inflammatory activity and suppresses lipid peroxidation. In the present study, we sought to elucidate the mechanistic basis for the neuroprotective and pro-angiogenic activity of engeltin in a human umbilical vein endothelial cells (HUVECs) oxygen-glucose deprivation and reoxygenation (OGD/R) model system and a middle cerebral artery occlusion (MCAO) rat model of cerebral ischemia and reperfusion injury. These analyses revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Rutin is a flavonoid from the same class of Q3G, which corroborates its antiangiogenic activity. Furthermore the literature reported that kaempferol interferes with VASH1 expression [ 36 ] and that engeletin regulates VASH2 [ 54 ], which is consistent with the regulation of both angiogenic factors by flavonoids.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Rutin is a flavonoid from the same class of Q3G, which corroborates its antiangiogenic activity. Furthermore the literature reported that kaempferol interferes with VASH1 expression [ 36 ] and that engeletin regulates VASH2 [ 54 ], which is consistent with the regulation of both angiogenic factors by flavonoids.…”
Section: Discussionsupporting
confidence: 68%
“…Flavonoids such as FAA [ 33 ] and vadimezan [ 34 ] interfere with tubulin; thus, they are grouped as VDAs. We speculate that Q3G is a VDA mainly because of its interference with VASH expression, similar to kaempferol [ 36 ] which regulates VASH1 and Engeletin [ 54 ] that acts on VASH2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, atherosclerosis is also the pathological basis of cerebral infarction and peripheral vascu- lar disease, and HCG11 is dramatically increased in AS patients [25]. Human umbilical vein colorectal cells are involved in CI/R injury [24], and HCG11 can regulate the proliferation of these cells and inhibit angiogenesis [12]. However, the role of HCG11 in CI/R injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Infarct brain tissues appear white, while normal brain tissues appear red. The sections were digitized, and the infarct areas were measured using Image Pro Plus software to calculate the percentage of cerebral infarct areas [ 22 ].…”
Section: Methodsmentioning
confidence: 99%